Artificial Neural Networks: Applications in Food Processing - Rauh, Cornelia; Delgado, Antonio; Park, Jinyoung; Kim, You Jin; Groß, Frauke; Diez Robles, Lucia (Reference Module in Food Science, 2016)
Artificial neural networks (ANNs) represent a mathematical approach that permits to mimic the learning process occurring in the brain of mammalians. The present article presents a short overview on ANNs. The basic need of the employment of ANNs in up-to-date food management systems, the theoretical background, and design of ANNs are described shortly. Examples of ANNs in food technology applications are also presented. The last section discusses current and future ANN methods in food technology.
Keywords: Artificial neural networks (ANNs); Food technology; Fuzzy logic (FL); Hybrid methods